Algebraic approach to differential equations - Lê, Dũng Tráng (World Scientific, 2010)
Mixing elementary results and advanced methods, "Algebraic Approach to Differential Equations" aims to accustom differential equation specialists to algebraic methods in this area of interest. It presents material from a school organized by The Abdus Salam International Centre for Theoretical Physics (ICTP), the Bibliotheca Alexandrina, and the International Centre for Pure and Applied Mathematics (CIMPA).